2020
DOI: 10.1038/s41419-020-2289-3
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene-dependent function of BRG1 in hepatocarcinogenesis

Abstract: Hepatocellular carcinoma (HCC) is the major type of primary liver cancer. Genomic studies have revealed that HCC is a heterogeneous disease with multiple subtypes. BRG1, encoded by the SMARCA4 gene, is a key component of SWI/SNF chromatin-remodeling complexes. Based on TCGA studies, somatic mutations of SMARCA4 occur in~3% of human HCC samples. Additional studies suggest that BRG1 is overexpressed in human HCC specimens and may promote HCC growth and invasion. However, the precise functional roles of BRG1 in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…Bai and colleagues showed that knockdown of BRG1 by RNAi greatly reduced breast cancer cell proliferation and induced cell cycle arrest [ 144 ]. BRG1 overexpression in human hepatocellular carcinoma samples further suggests that BRG1 can function in both tumor suppressing and oncogenic capacities depending upon oncogenic stimuli [ 145 ]. The potential therapeutic effects of targeting of BRG1 ATPase activity were recently assessed [ 146 , 147 ].…”
Section: Gbaf and Its Subunits In Mammalian Diseasementioning
confidence: 99%
“…Bai and colleagues showed that knockdown of BRG1 by RNAi greatly reduced breast cancer cell proliferation and induced cell cycle arrest [ 144 ]. BRG1 overexpression in human hepatocellular carcinoma samples further suggests that BRG1 can function in both tumor suppressing and oncogenic capacities depending upon oncogenic stimuli [ 145 ]. The potential therapeutic effects of targeting of BRG1 ATPase activity were recently assessed [ 146 , 147 ].…”
Section: Gbaf and Its Subunits In Mammalian Diseasementioning
confidence: 99%
“…It is of intrigue to note that there appears to be a striking similarity in terms of the pathobiological processes that BRG1 and CK2 seem to co-regulate although no prior study has ever linked one to the other. BRG1 and CK2 can both regulate SREBP-dependent lipogenesis [ 35 , 98 ], liver regeneration [ 32 , 99 ], and hepatocellular carcinoma [ 100 , 101 ]. Further studies are warranted to address whether there is a universal co-dependency between BRG1 and CK2 in liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin remodeling is essential for gene transcription, DNA replication, and DNA repair [ 78 ] that is governed by multiple protein complexes. Mutations in chromatin regulator SMARCA4, AT-rich interaction domain (ARID) 1A, ARID1B, ARID2, myeloid/lymphoid leukemia (MLL), MLL3, and bromodomain PHD finger transcription factor (BPTF) genes contribute to HCC [ 79 , 80 ].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%